Improvement of both lipid and biomass productivities of Qatar Chlorocystis isolate for biodiesel production and food security. Issue 3 (29th May 2018) - Saadaoui, Imen; Bounnit, Touria; Muraikhi, Maryam; Rasheed, Rihab; Alghasal, Ghamza; Al Jabri, Hareb
SUMMARY: Microalgae are considered a very promising alternative for biofuel production. Several strategies were developed to modulate and improve algae metabolites production to meet the requirements for biodiesel production. Most previous research evidenced that the increase of the lipid content is accompanied by a decrease of the biomass production, which increases the cost of the downstream processing. Hence, the challenge is to find special culture conditions that increase the lipid and the biomass productivities simultaneously. In the present work, we developed a strategy for the improvement of biomass and lipid productivities in a novel local microalga isolate, Chlorocystis sp. QUCCCM14, which was not previously known as a promising strain. Indeed, culturing QUCCCM14 using f/2 medium with 10× NaH2 PO4 (0.15 g L −1 NaNO3 and 5.6 mg L −1 NaH2 PO4 ) resulted in an improvement of 3.178 folds the lipid productivity reaching 56.121 mg L −1 day −1 and enhanced the biomass productivity reaching 141.363 mg L −1 day −1, simultaneously. Comparative analyses of the FAME profiles demonstrated that fed‐batch culture with phosphate or nitrate separately leads to a high production of the omega 3 fatty acids (Linolenic acid), whereas fed‐batch culture with phosphate and nitrate simultaneously increased the production of fatty acids suitable for biodiesel production.